2016
DOI: 10.1016/j.jvs.2015.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Tibial and peroneal bypasses in octogenarians and nonoctogenarians with critical limb ischemia

Abstract: Our analysis showed good results in octogenarians undergoing tibial and peroneal bypass surgery with regard to patency rates and limb salvage. However, octogenarians had a significantly higher perioperative mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Previous studies have demonstrated the benefit of bypass to the peroneal artery for pedal gangrene. [1][2][3] In patients with tissue loss (ulcer or gangrenous pedal lesions) and a peroneal artery as the only patent artery in the leg, choices for revascularization are limited to peroneal bypass. Whereas peroneal bypass requires less autogenous conduit than inframalleolar bypass, its efficacy depends on the patency of its branches.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated the benefit of bypass to the peroneal artery for pedal gangrene. [1][2][3] In patients with tissue loss (ulcer or gangrenous pedal lesions) and a peroneal artery as the only patent artery in the leg, choices for revascularization are limited to peroneal bypass. Whereas peroneal bypass requires less autogenous conduit than inframalleolar bypass, its efficacy depends on the patency of its branches.…”
mentioning
confidence: 99%
“…Their patency rates were similar when compared with controls 19 . Even in more complex below-the-knee revascularization procedures, outcomes of octo- and nonagenarians are satisfying with regard to patency rates and limb salvage 20 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In total, five of the 21 studies were considered to be of higher methodological quality (!7 points). Six studies investigated endovascular revascularisation only, 16,21,23,26,29,32 six studies investigated surgical revascularisation only, 17,20,27,28,31,34 and nine analysed both techniques. 10,15,18,19,22,24,25,30,33 In addition, in five studies a subgroup of patients was treated conservatively and four studies investigated outcomes after primary amputation as well.…”
Section: Study Characteristics and Patient Demographicsmentioning
confidence: 99%